PENERAPAN RELAKSASI OTOT PROGRESIF SEBAGAI UPAYA PEMENUHAN ISTIRAHAT DAN TIDUR PADA LANSIA DI PUSKESMAS TANJUNG BALAI KARIMUN - Maria Menda; Sarmauli Franshisca Sihombing (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
Symptoms of insomnia often occur in the elderly (elderly), even almost half of the elderly reported having difficulty starting sleep in maintaining their sleep, as many as 50-70% of all elderly aged > 65 years. Treatment of insomnia can be done with non-pharmacological and pharmacological therapies. Non-pharmacological therapies, especially behavioral therapies, are effective for chronic insomnia in the elderly, which consist of several methods, namely Progressive Muscle Relaxation, sleep restriction, stimulus control, sleep hygiene and cognitive behavioral therapy. The aim of the study is to provide comprehensive and continuous midwifery care for elderly mothers, with management of midwifery care in accordance with midwifery service standards. Midwifery care that is applied is progressive muscle relaxation to meet the sleep needs of the elderly. The research method used in the preparation of practice reports is descriptive research using the case study method. Recommendations that can be given to the elderly are general behavior, especially suggestions about healthy sleep practices